Mean platelet volume and red cell distribution width to platelet ratio for predicting the severity of hepatic fibrosis in patients with chronic hepatitis C. Issue 7 (July 2016) - Karagöz, Ergenekon; Tanoğlu, Alpaslan; Ülçay, Asim; Erdem, Hakan; Turhan, Vedat; Kara, Muammer; Yazgan, Yusuf
Abstract : Objective: We designed this study to investigate the relationship between the severity of fibrosis and mean platelet volume (MPV), red cell distribution width, and red cell distribution width to platelet ratio (RPR) in patients with chronic hepatitis C (CHC). Design: Overall, 98 biopsy-proven naïve CHC cases were enrolled in the study. Complete blood count variables, including white blood cell, hemoglobin, platelet count, MPV, red cell distribution width, platelet distribution width as well as aspartate transaminase, alanine transaminase, total bilirubin, albumin, and other routine biochemical parameters, were tested. Liver biopsy samples were assessed according to the Ishak scoring system. Data analyses were carried out using SPSS-15 software. Statistical significance was set at a P -value of less than 0.05. Results: Of the 98 cases, 80 (81.6%) were men and 18 (18.4%) were women. Fibrosis scores of 69 cases (70.4%) (group 1) were less than 3, whereas 29 cases had fibrosis scores at least 3 (29.6%) (group 2). Significant differences in MPV and RPR were observed between these two groups (MPV: 8.19±1.002 vs. 8.63±0.67 fl, P <0.05; RPR: 0.0526±0.02 vs. 0.0726±0.02, P =0.001). The areas under the curve of the RPR and MPV for predicting significant fibrosis were 0.705 and 0.670, which was superior to the aspartate transaminase-to-alanine transaminase ratio and aspartate transaminase-to-platelet ratio index scores of the study group. Cut-off values were calculated for diagnostic performance, and the cut-off values for MPV and RPR were 8.5 and 0.07 fl, respectively. Conclusion: MPV and RPR values were significantly higher in patients with CHC, associated with severity, and can be used to predict advanced histological liver damage. The use of MPV and RPR may reduce the need for liver biopsy. Further studies are required to determine the relationship between these parameters and the severity of fibrosis in hepatitis C patients.